Pengamanahan Dalam Perancangan Dan Pengurusan Harta Orang Islam - Noor Lizza Mohamed Said; Wan Amirul Adli Wan Ayub; Mohd Zamro Muda; Mohd Izhar Ariff Mohd Kashim; Adnan Mohamed Yusoff (UKM Press, 2024)
Non-Indexed Publication